MENJAGA INDEPENDENSI MA DARI KEKUASAAN PEMERINTAH MAUPUN KEKUASAAN LAINNYA - Poltak Siringoringo (to-ra, 2018)
The 1945 Constitution article 24 paragraph (1) power is exercised by a Supreme Court and others The Judiciary according to the law and the Elucidation of the 1945 Constitution is said: Judicial Power is an independent pow- er, meaning that it is independent of government authority. However, in 32 years the New Order government was in power, the independence of the Supreme Court and judicial authority were put in place, the Supreme Court as a judicial institution in carrying out its duties was always in uenced by the government (in uenced by executive power). Thus what was started in the explanation of the 1945 Constitution above, namely judicial power is an independent power or a power that is independent of government power is not carried out according to the law, but is carried out according to the wishes of the Orde Baru Era. Keyword : constitution; guaranteed; supreme court; Orde Baru Era; executive power.